2020
DOI: 10.3389/fpsyg.2020.01379
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin–Italian Dual-Language Children’s Comprehension of Head-Final and Head-Initial Relative Clauses

Abstract: The acquisition of languages by children using two languages is a matter of debate as many factors contribute to the success of this type of acquisition. We focus on how the competence of dual-language children changes in their two languages as a function of length of exposure and establish whether there are reciprocal influences during language development. We examined the comprehension of subject and object relative clauses in a group of 6-year-old (younger) and 8-year-old (older) Mandarin-Italian dual-langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…As pointed out by one anonymous reviewer, Hu, Costa and Guasti (2020) found that when bilingual children did not comprehend object RCs, they were more likely to make embedded Errors (Middle errors in this paper) in Mandarin; whereas, in this paper, children with SLI were prone to making reversal errors when they had trouble interpreting Mandarin object RCs. This discrepancy will be investigated further in the future.…”
Section: Discussionmentioning
confidence: 53%
“…As pointed out by one anonymous reviewer, Hu, Costa and Guasti (2020) found that when bilingual children did not comprehend object RCs, they were more likely to make embedded Errors (Middle errors in this paper) in Mandarin; whereas, in this paper, children with SLI were prone to making reversal errors when they had trouble interpreting Mandarin object RCs. This discrepancy will be investigated further in the future.…”
Section: Discussionmentioning
confidence: 53%